2021
DOI: 10.3389/fpos.2021.662687
|View full text |Cite
|
Sign up to set email alerts
|

Motivators of Participation and Non-Participation in Youth Environmental Protests

Abstract: This paper is an exploratory study investigating motivators of teenagers to both attend and not attend a climate change related protest event. Using open-ended surveys and focus groups, 16–19-year-old Australian students were asked about their motivators to attend and abstain from School Strike 4 Climate events. Through qualitative analysis and thematic coding, results show key motivators to attend a Strike include climate change and acts of political participation that provide youth with a public voice. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…That is to say, structures of governance within a school can lead to '"no pedagogically acceptable language" to contest school practices' (Mayes, 2020, p. 460). For example, in my own research, positive relationships with school executives have led to 'nominations' of exemplar students to be the face of their school in our discussions of the School Strike (Feldman, 2021). This governmentality may limit opportunities for students (whether cognisant or not) to freely criticise the powers that influence their daily lives and choices around the School Strike.…”
Section: Implications: Methods and Practicementioning
confidence: 98%
See 3 more Smart Citations
“…That is to say, structures of governance within a school can lead to '"no pedagogically acceptable language" to contest school practices' (Mayes, 2020, p. 460). For example, in my own research, positive relationships with school executives have led to 'nominations' of exemplar students to be the face of their school in our discussions of the School Strike (Feldman, 2021). This governmentality may limit opportunities for students (whether cognisant or not) to freely criticise the powers that influence their daily lives and choices around the School Strike.…”
Section: Implications: Methods and Practicementioning
confidence: 98%
“…We see this in the School Strike 4 Climate case, where parental or academic control may be influencing participation in a Strike (see, e.g. Feldman, 2021). For example, many state-level administrators currently only enable youth participation in research via parental consent, even with older, upper high school students in the public system.…”
Section: Implications: Methods and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have worked to identify the underlying motivations young people have for becoming climate activists. Governmental inaction and the sense that politicians are failing them is a common source of motivation; this is true among young climate strikers in the UK (Pickard et al, 2020;Elsen and Ord, 2021;Feldman, 2021) and is a common narrative in the Fridays For Future movement as a whole (Han and Ahn, 2020). Haugestad et al (2021) and Martiskainen et al (2020) found a variety of motivations for participation among climate strikers in Canada, the USA, the UK (Martiskainen et al, 2020) and Norway (Haugestad et al, 2021).…”
Section: How Young People Come Into Climate Actionmentioning
confidence: 99%